Penyuluhan Digital Branding Pada UMKM Berbasis Food And Beverage Di RW 09 Kelurahan Klampis Ngasem - Erliniatus Nur Rohma; Nabil Ghibran Alwafa; Talitha Naila Niazi; Roziana Febrianita (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Technological advances will continue to develop over time and cannot be avoided, there will always be new innovations created with the aim of helping various human activities. Of course, the people in the Klampis Ngasem Sub-District themselves understand more or less the use and benefits of the internet, but there are still many people, especially MSMEs players in RW 09 who do not really understand the benefits of current technological advances, especially in selling their products. On this basis, the urgency of having community service activities with the theme of digital branding counseling at food and beverage-based MSMEs in RW 09, Klampis Ngasem is to provide insight to counseling participants, especially MSMEs actors, regarding the importance of business branding (logo and packaging) and the economy. creative to find innovation and creativity in developing their business in today's new industrial era. The output resulting from this service activity is appropriate technology (TTG) in the form of a mini box studio, scientific articles published in national journals, and activity reports. In this activity the results obtained are the use of a digital branding strategy that can be continued with regular assistance so that MSMEs actors can be optimal in marketing and increasing sales.